Executive Functions, Motor Development, and Digital Games Applied to Elementary School Children: A Systematic Mapping Study - Victória Branca Moron; Débora Nice Ferrari Barbosa; Gustavo Roese Sanfelice; Jorge Luis Victória Barbosa; Daiana R. F. Leithardt; Valderi Reis Quietinho Leithardt (MDPI AG, 2022)
Studies show that executive functions and motor development are associated with each other and with learning ability. A more technological lifestyle combined with digital culture should be considered a viable alternative to stimulate children's development. Therefore, this study aimed to present a systematic mapping of the literature involving executive functions, motor development, and the use of digital games in intervention programs for elementary school children from 6 to 11 years old. Four databases were researched: PubMed, Scielo, Science Direct, and SCOPUS, including publications between 2012 and March 2021. The initial results indicated 4881 records. After the selection process, 15 manuscripts that presented the central theme of the study were selected. The main results indicated that intervention strategies are rather heterogeneous. Most of the studies demonstrated efficient results after intervention protocols, many of them were conducted in Europe, and 46% occurred in a school environment. No research was identified involving technological solutions using executive functions, motor development, and digital games in an integrated manner. Hence, this constitutes a field of future scientific research.